Generalized hypertrichosis due to secukinumab in a patient with moderate psoriasis: A case of serendipity or zemblanity?. Issue 3 (17th April 2019) - Sacchelli, Lidia; Magnano, Michela; Patrizi, Annalisa; Bardazzi, Federico
Abstract: After 4 months of therapy with secukinumab, a 67‐year‐old man with moderate psoriasis developed generalized hypertrichosis, along with PASI 90. The patient denied any drug intake, apart from secukinumab, nor applications of any creams. Moreover, this event did not really bother the patient, thus the therapy was not discontinued and the hypertrichosis is persisting as psoriasis' control.